Hugh Broughton (1549-1612): scholarship, controversy and the English Bible - Macfarlane, K (2017)
This thesis provides a revisionist account of the relationship between Latin biblical criticism, vernacular religious culture and Reformed doctrines of scriptural authority in the early modern period. It achieves this by studying episodes from the career of the English Hebraist Hugh Broughton (1549-1612). Current orthodoxy holds that Broughton’s devotion to the tenets of Reformed scripturalism distinguished him from contemporary biblical humanists, whose more flexible attitudes to the Bible enabled them to produce cutting-edge scholarship. In challenging this consensus, this thesis focusses on three areas. The first is chronology. Recent work has presented chronology as divided between technical, philological practitioners, who drew from astronomy and humanism alike in their efforts to date the past, and scripturalists, who relied on the Bible alone. Using the chronological controversy between Broughton and the Oxonian John Rainolds, this thesis complicates this picture by arguing that both approaches to the discipline were equally derived from humanistic traditions, and that confessional, rather than intellectual or methodological, factors informed the most important decisions chronologers made. The second area is biblical criticism. There is still a broad assumption that Reformed beliefs about scripture were incompatible with the most advanced biblical scholarship. This thesis questions such assumptions by reconstructing Broughton’s research into the Hebraic contexts of the New Testament. By demonstrating that it was possible to produce innovative and influential work without challenging and indeed, while endorsing the principles of Reformed scripturalism, this thesis disputes current teleological presumptions about the development of modern, historical biblical criticism. The third is the history of lay reading. Both chronology and biblical criticism have often been viewed as specialised pursuits, studied only by a Latin-reading elite and irrelevant to lay people. For Broughton and his followers, however, biblical scholarship and lay piety were inseparable. The thesis demonstrates this by piecing together Broughton’s radical plans for a new English Bible, including his work with John Speed on biblical genealogy, and his revisions of the Geneva New Testament. Using numerous neglected manuscript sources, it gives an account of the sixteenth-century biblical translation that foregrounds the unexpected ways in which groundbreaking neo-Latin, continental biblical scholarship expanded scholars' concepts of what vernacular translation could achieve.